PENGARUII DEPOSITO, PENYALURAN }CREDIT NON-SME TERHADAP NET INTEREST MARGIN SEKTOR PERBANKAN TAHUN 2010 SAMPAI TAHUN 2014 - Feranika Husodo (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2017)
This study aims to examine the effect of deposits and credit distribution on the banking net interest sector. Observation period from 2010 to 2014. The total bank sample used was 111 banks included in the BUKU 1 bank category until BUKU 4. The analytical techniques used were related to hypothesis testing using multiple linear regression panel data. The results show that deposits have a positive and significant effect on net interest margins, while lending has a negative and significant effect on net interest margins.